Materials analysis by ion channeling at "Demokritos" - Harissopulos, S.; Kossionides, S.; Paradellis, T.; Maggiore, G. (HNPS Advances in Nuclear Physics, 2020)
A new fully automated Goniometer system installed recently at the Institute of Nuclear Physics of "Demokritos" is presented. This system enables to perform materials analysis not only via the Rutherford Backscattering method, which has been used so far at "Demokritos", but also by the ion channeling technique. The first experiments carried out using the Goniometer are also presented.